THE QUALITATIVE INVESTIGATION IN EDUCATION - Loayza Maturrano, Edward Faustino (2014)
This paper approaches educational research from a qualitative perspective of analysis. Teachers trying to implement an investigation in this field should use, at best, both conceptions of research: quantitative and qualitative. Evidently, this will depend on the scientific context, due to the fact that a great proportion of research in the educational field demands an adequate reaction to the reality. First, we analyze the problem of scientific progress in the educational field. Then, we analyze the application limitations of quantitative investigation in education; as well as the possibilities of qualitative research. Later, we carry out main procedures of qualitative investigation. Finally, we carry out a comparison of both research models.